Los niños y niñas transgénero y su derecho a la identidad y a la identificación en la Legislación Ecuatoriana. - Albán Alvarado, Karla Jeanneth (2024)
Through this research work, titled "Transgender Children and Their Right to Identity and Identification in Ecuadorian Legislation" it addresses one of the most pressing and concerning issues in recent times in Ecuadorian society. It pertains to the realization of the rights of those children who do not identify with the gender they were assigned at birth. Nowadays, we see children as young as 5 or 6 years old expressing a preference for a gender different from their biological one. There are girls who feel biologically trapped in a body that doesn't match their identity, and vice versa. Today, their parents have embarked on a challenging battle to ensure that these transgender children can lead normal lives within society, especially within educational institutions, where this group of children often faces significant challenges. From a legal perspective, it is necessary to conduct an objective legal analysis to examine the situation of transgender children and their rights in Ecuadorian legislation. While it is true that the Constitution of the Republic categorizes children as a group of top-priority concern, protected by the principle of the best interests of the child, the Code of Childhood and Adolescence outlines the principles under which their rights should be applied, as also established in this legal framework. However, issues have arisen concerning the right to identity and identification. The Civil Registry does not currently allow a child to change their name to that of the opposite gender. The most serious issues in this regard occur during the children's schooling years, as institutions, through their authorities, teaching staff, and students, express their prejudices in the most insensitive manner. Often, there is no law to protect this group of children. This is where arrises the need to legally establish the right to identity and identification for all children equitably, without discrimination based on race, religion, belief, culture, or sexual orientation. 5 In this research work, I will analyze iconic cases that have taken place in Ecuador with the aim of assessing the progress that legislation has made in this regard, respecting the freedom of decision and thought of individuals from childhood. The methodology to be applied in this research is descriptive and explanatory. It is necessary to describe the social phenomenon by investigating literature, legal norms, and practical cases that have already occurred in Ecuador on this subject. This will be complemented by the explanatory aspect, which will allow me to establish the causes and effects of the studied phenomenon, make connections, and draw conclusions. Additionally, I will use the dogmatic and interpretive method of constitutional and legal norms, as these methods provide a response to the addressed problem. Keywords: transgender, identity, identification, equity principle, right, guarantee, principle.